Design and Evaluation of AI-Based Musyarakah Sales System at UMKM XYZ Tangerang - Bambang Judi Bagiono; Nasirudin Nasirudin; Joko Sarono (PT. Student Rihlah Indonesia, 2026)
The rapid development of digital technology and Artificial Intelligence (AI) has significantly transformed business governance, particularly among Micro, Small, and Medium Enterprises (MSMEs). Sharia-based MSMEs applying musyarakah contracts frequently face managerial challenges due to manual transaction recording and profit-sharing calculations, leading to computational errors, reporting delays, and limited transparency. This study designs and evaluates an AI-based remotized musyarakah sales management system at UMKM XYZ Tangerang using a compound percentage method. A mixed-methods approach was employed, involving observation, in-depth interviews, and financial document analysis. The system was tested over a 12-month period, analyzing 1,080 sales transactions (540 before and 540 after implementation). The web-based platform enables partners to remotely monitor real-time sales and profit-sharing data. The compound percentage method calculates profit distribution proportionally based on capital contribution, operational involvement, and managerial responsibility. Quantitative results show that profit-sharing calculation accuracy increased from 88% to 97%, reporting time decreased by 35%, and financial discrepancies were reduced by 42%. Revenue forecasting accuracy reached 93% using machine learning models. Operational efficiency improved by 30%, while partner satisfaction scores increased from 3.4 to 4.5 (on a 5-point scale). These findings demonstrate that integrating Islamic financial principles with AI-driven systems enhances transparency, efficiency, and sustainable Sharia-compliant MSME growth.